2022
DOI: 10.1186/s12884-022-05227-4
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding-oriented education for parturients separated from their hospitalized infants: a qualitative study of nurses’ perspectives in Shanghai, China

Abstract: Background The benefits of breastfeeding for both mother and baby are well recognized. However, the separation of the mother-newborn dyad leads to a lower breastfeeding rate. These parturients who are separated from their hospitalized infants are sometimes unaware of the importance of breastfeeding, while nurses do know how important health education on breastfeeding is and how it can be improved. This descriptive qualitative study aimed to explore the experiences of nurses regarding health edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…If persons with low self-efficacy fail, they will blame themselves, whereas persons with high self-efficacy are prepared to test and try until they reach a solution. Based on the Feng study [ 35 ], we found that mothers of preterm infants reported physically and mentally challenging breastfeeding experiences during the period they were separated from their infants. Most mothers and family members of preterm infants lack breastfeeding knowledge and skills, especially expressing breastmilk and establishing lactation.…”
Section: Discussionmentioning
confidence: 99%
“…If persons with low self-efficacy fail, they will blame themselves, whereas persons with high self-efficacy are prepared to test and try until they reach a solution. Based on the Feng study [ 35 ], we found that mothers of preterm infants reported physically and mentally challenging breastfeeding experiences during the period they were separated from their infants. Most mothers and family members of preterm infants lack breastfeeding knowledge and skills, especially expressing breastmilk and establishing lactation.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization recommends exclusive breastfeeding for the first 6 months after childbirth [ 2 ]; however, only approximately 40% of infants younger than 6 months are exclusively breastfed [ 3 ]. The global exclusive breastfeeding rate is low at 33% [ 4 ], with approximately 29.2% and 25% in China and Europe, respectively [ 5 , 6 ]. PH is the most frequently reported reason for discontinuing breastfeeding [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%